THE ROLE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE DEVELOPMENT OF SOCIETY. - Abdusamadova Mukarramxon Baxtiyorjon qizi,; Fakhriddin Urinboevich Toshboltaev, (Ustozlar uchun, 2025)
This article provides an in-depth analysis of the role of information and communication technologies (ICT) in the development of society. It discusses how technological development affects every aspect of modern human life, the impact of ICT on socio-economic spheres, digital transformation, artificial intelligence, remote services, and changes in the education system. The article serves to demonstrate the effective use of ICT in society and reveal its future potential.